Bridging the knowing-doing gap: Researching a new approach to disability and employment programming. - Rudstam, Hannah; Hittleman, Margo; Pi, Sukyeong; Gower, Wendy Strobel (Journal of Vocational Rehabilitation, 2013)
Despite significant program efforts since the ADA was passed in 1990, the employment rates of people with disabilities have changed little. While the causes behind these disappointing outcomes are multi-facetted and complex, it is clear that a knowing-doing gap has limited the effectiveness of efforts to change these disappointing statistics. That is, though employers have a basic knowledge of the ADA, this knowledge is largely not being translated into actions or practices. Approaches are needed that go beyond merely disseminating information to actively engage employers in bringing about organizational change. We designed, implemented and researched a program aiming to bridge the knowing-doing gap. This program was based on a blended learning approach designed to build organizational change strategies and partnerships. A comprehensive program research effort included both a measure of immediate program impact (using the BIAT - a researcher-developed and validated tool) and longer-term impact (using a grounded theory, open-ended interviewing protocol). Implications for further research and practice are discussed using findings from both the short-term and long-term studies.